Tax Avoidance in Energy Companies: The Roles of ESG, Capital Intensity, and Transfer Pricing - reza shah fahrezi; Yuni Putri Yustisi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The main focus of this study is to analyze the impact of three key factors: Environmental, Social, and Governance (ESG), Capital Intensity, and Transfer Pricing, on tax avoidance practices among companies in the Indonesian energy sector, using the Effective Tax Rate (ETR) as an indicator. This research is motivated by the increasing public demand for fiscal transparency and the widespread cases of tax avoidance through profit shifting, as seen in the Adaro Energy case, which highlights the complexities of tax governance in the energy sector. The testing was conducted using a quantitative method with multiple linear regression analysis (via SPSS) on 132 observations of energy companies during the period 2021–2024. This study found that ESG has a significant negative impact on tax avoidance practices, while capital intensity has a significant positive impact on these practices. Transfer pricing was not found to have a significant effect. The conclusion of these findings underscores the crucial role of sustainability practices (ESG) and corporate asset structure in shaping tax behavior, while also highlighting the need for stricter oversight of related-party transactions. This research is expected to provide a substantive contribution to the development of academic literature and to offer strategic recommendations for regulators in formulating tax policies that are more adaptive and effective in line with the evolving dynamics of the energy sector.